Nanofat injector: a low-cost disposable device for standardization and optimization of grafting time - João Maximiliano; Mirian Pedron; Antonio Carlos Pinto Oliveira; Eduardo Madalosso Zanin; Daniele Walter Duarte; Ciro Paz Portinho; João Luiz Martins; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Nanofat graft improves skin quality in damage secondary to aging and scar sequelae. We present the initial results of the nanofat graft using a low-cost disposable device, proposing a standardization of its use according to the area to be treated. Methods: A prospective cohort was conducted from July 2019 to March 2020. The inclusion criterion was patients who underwent nanofat grafting for skin treatment. The exclusion criterion was the previous performance of some invasive treatment of the skin. Twenty consecutive patients who met the prerequisites were analyzed. The results were evaluated in the 6th postoperative month. The patients answered a questionnaire, classifying from 1 - very bad to 10 - excellent, changes in skin quality. Results: The twenty patients followed did not present any postoperative complications. Edema after the application was reduced between three and seven days. There was no hematoma or infection. Patients who underwent only nanofat grafting without another associated surgery could return to their activities after 24 hours. The scores reported by patients at 6 months were between 7 and 10, with a mean of 8. Conclusion: The use of the SmartneedleTM system for nanofat grafting presents patient satisfaction similar to other application methods and allows a uniform and standardized distribution of the graft according to the anatomical region and optimizing surgical time